2020
DOI: 10.1145/3422869
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Empirical Measures of Workload Capacity

Abstract: The usability of the human-machine interface is dependent on the quality of its design and testing. Defining clear criteria that the interface must meet can assist the implementation and evaluation process. These criteria may be based on performance, the quality of users’ experience, error prevention, or the broad utility of the interface. In this article, we motivate the use for workload capacity as an empirical measure of usability. We first describe generic and specific uses for work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…High mental workload has been associated with accident risk in various work domains (e.g., Chen, Song, & Lin, 2016;Habib, Shalkamy, & El-Basyouny, 2019). There are a variety of subjective and objective measures of workload (Charles & Nixon, 2019;Matthews, Reinerman-Jones, Barber, & Abich, 2015;Thorpe, Nesbitt, & Eidels, 2020). In general, they are all based on the assumption that workload will vary as a function of task demand and the limited human information-processing resources available to meet those demands (Gopher, & Donchin, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…High mental workload has been associated with accident risk in various work domains (e.g., Chen, Song, & Lin, 2016;Habib, Shalkamy, & El-Basyouny, 2019). There are a variety of subjective and objective measures of workload (Charles & Nixon, 2019;Matthews, Reinerman-Jones, Barber, & Abich, 2015;Thorpe, Nesbitt, & Eidels, 2020). In general, they are all based on the assumption that workload will vary as a function of task demand and the limited human information-processing resources available to meet those demands (Gopher, & Donchin, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with previous reviews, we identified the application of subjective measurement methods to be the most frequently used approach for the assessment of the MWL. [ 66 ]. Although we were able to identify a most frequently applied method, one of the main findings of this review was the heterogeneity of applied assessments, which is also in line with previous analyses [ 20 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, none of the studies mentioned in this section explicitly addresses the relationship between MWL and HIS/DHT. Many studies also consider MWL as a starting point for further consequences on the performance of the HCPs, for example, a hazard to patient safety or job satisfaction (66), rather than the factors contributing to a high MWL.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…Cognitive load has many descriptions, generally, it is the application of mental resources to deal with the strain caused by the workload of a task and to reach the task's completion. (Thorpe, Nesbitt, & Eidels, 2020;Young, Brookhuis, Wickens, & Hancock, 2015). There is a well-established effect of cognitive load on performance outcomes.…”
Section: Cognitive Load and Performance Outcomesmentioning
confidence: 99%